Indonesia's Breakthrough in Efficient Shellfish Cleaning Transforms Seafood Industry: Terobosan Indonesia dalam Pembersihan Kerang yang Efisien Mengubah Industri Makanan Laut - Setiawan, Ari Rio De; Jakaria, Ribangun Bamban; Sari , Indah Apriliana; Sukmono, Tedjo (Indonesian Journal of Innovation Studies, 2024)
This research aims to design an efficient cleaning tool for bloody cockles to help business actors meet high demand with limited production systems. Conducted in Sidoarjo, data was collected from literature, government reports, and interviews with local business actors, revealing that manual processing of 50 kg of cockles takes 6-8 hours. Using the morphological method, several design concepts were evaluated for maintenance ease, performance, safety, and durability. The selected design (concept 3) showed the highest efficiency with a 37.5% score. This tool is expected to reduce cleaning time and improve outcomes, enhancing productivity and quality in the seafood processing industry. Highlight: Efficient Design: Reduces cleaning time from 6-8 hours significantly. High Demand: Meets increased consumer demand with limited resources. Optimal Concept: Concept 3 excels in maintenance, safety, and efficiency. Keywoard: Bloody Cockles, Cleaning Tool, Morphological Method, Efficiency, Seafood Processing